Impact of the System of Rice Intensification (SRI): analysis of SRI practices in 13 states of India. - Kuppannan, Palanisami; Karunakaran, K. R.; Amarasinghe, Upali A. (International Water Management Institute, 2012)
The System of Rice Intensification (SRI) - a package of practices designed to grow more rice with less water - is being widely promoted by governments and NGOs in India. In 2010-11, IWMI-Tata Program, in collaboration with local partners, undertook a study covering 2234 rice farmers in 13 major rice growing states to analyze the adoption level and impact of various SRI practices. The results confirm that SRI adopters, on the whole, displayed comparatively higher yield, higher gross margin and lower production costs. However, most ?SRI farmers? in the study sample did not adopt the full package of practices due to several constraints. In fact, only 20 percent could be classified as ?full adopters? while the rest were ?low adopters? or ?partial adopters?. This highlight argues that a targeted approach that offers farmers flexibility in adopting a sub-set of SRI practices in accordance with the local resources conditions can have a significant impact on paddy productivity.